2020
DOI: 10.1109/access.2020.2985163
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Time-Reversal Based Far-Field Wireless Power Transfer From Antenna Array in a Complex Environment

Abstract: The performance of time-reversal (TR) based far-field wireless power transfer (WPT) from an antenna array in a complex propagation environment is investigated in comparison with conventional arraybased beamforming (BF). A two-step experiment is performed, namely 1) the propagation stage and 2) rectification stage. In the propagation stage, signal transmission is measured between the transmit array and receive antenna in an indoor multipath environment, for line-of-sight (LOS) and non-line-of-sight (NLOS) scena… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…According to (5) and considering that θ m,n = θ n,m , φ m,n = −φ n,m , ( 6) is expressed in a finite series form, as follows ( 7), with the radiation patterns of Tx and Rx single elements. Given that this principle is equally applicable to all N -elements in the Rx array, the total received power (P R ) can be expressed as (8), assuming that each instance of individual power received is synthesized without loss.…”
Section: Principle Of the Proposed Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to (5) and considering that θ m,n = θ n,m , φ m,n = −φ n,m , ( 6) is expressed in a finite series form, as follows ( 7), with the radiation patterns of Tx and Rx single elements. Given that this principle is equally applicable to all N -elements in the Rx array, the total received power (P R ) can be expressed as (8), assuming that each instance of individual power received is synthesized without loss.…”
Section: Principle Of the Proposed Methodsmentioning
confidence: 99%
“…Even with low WPT efficiency, defined as the ratio of the total received power (P R ) reaching the Rx antenna to the total transmitted power (P T ) radiated from the transmitter (Tx) antenna, it is possible to increase the WPT efficiency by applying an array with multi-elements as Tx or Rx antenna. In addition, beamforming technology with an array antenna ensures wireless power transfers in specific directions [3]- [5]. Accordingly, many studies related to array antennas and beamforming have been conducted in an effort to improve the RF WPT efficiency [6]- [10].…”
Section: Introductionmentioning
confidence: 99%
“…The performance of TR-WPT in comparison to conventional beamforming (BF) based WPT was investigated. The results show that TR achieves higher peak voltages at the receiver compared to BF under the same average transmit power in an indoor multipath environment [18]. In particular, TR can take advantage of rich multipath to deliver more power at the desired locations, especially in complex multipath environments such as factories or indoor rooms [19].…”
Section: Introductionmentioning
confidence: 95%
“…TR can outperform BF with higher rectification efficiency given the same average transmit power. 24 Based on the superiorities of adaptive spatiotemporal focusing of TR, a method and algorithm to charge multi-powered devices wirelessly in 3D indoor environments are presented. 25 In this article, we investigate the feasibility of employing a group of point focusing fields (PFFs) to transmit multiple binary bits in parallel to a single receiver.…”
Section: Introductionmentioning
confidence: 99%
“…However, it is shown that the signals received using TR lead to higher rectified DC voltage and rectification efficiency. TR can outperform BF with higher rectification efficiency given the same average transmit power 24 . Based on the superiorities of adaptive spatio‐temporal focusing of TR, a method and algorithm to charge multi‐powered devices wirelessly in 3D indoor environments are presented 25 …”
Section: Introductionmentioning
confidence: 99%